PELATIHAN PEMBUATAN BATIK JUMPUTAN DAN PEMASARAN PRODUK MELALUI MEDIA DIGITAL DESA GONILAN KECAMATAN KARTASURA - Ratna Herawati; Dessyana Kardha (Sekolah Tinggi Ilmu Ekonomi AMA, 2023)
Gonilan Village, Kartasura District, Sukoharjo Regency was geographically located in the northernmost part of Sukoharjo Regency. This location was not far from Surakarta city, made it a busy area among other areas. The social differences that occur in there made the community form clusters, between the majority of investment owners and the minority, namely native residents who didn’t have excess land for investment and earn income as laborers. Training and assistance on product innovation and marketing was needed as an effort to train entrepreneurs to improve the creative economy of them. This community service aimed to provided knowledge about techniques for making jumputan and marketing products throught social media. This training was carried out in three stages, planning, namely communication with the head of the Gonilan PKK driving team. The implementation was divided into two, namely jumputan making training and digital marketing training, and the final stage was evaluation to follow-up to further activities. Overall, the training has been carried out well. Implementers carry out training and mentoring through program demos, lectures and questions and answers with training participants. Training participants have increased abilities and skills in entrepreneurship. Knowledge about digital marketing is also increasing.